All fiber spatiotemporal mode-locked fiber laser at 1.55 μm delivering multimode conventional solitons or bound solitons. (August 2022) - Guo, Tiegang; Wang, Zhaokun; Gao, Feng; Zhao, Chunliu; Chang, Shuo; Zhang, Xuebin
Highlights: The laser system is a hybrid all fiber erbium-doped laser composed of single-mode (SM) and multimode (MM) fiber segments. Three different kinds of multimode solitons at ∼ 1560 nm are generated, including the conventional solitons, loosely bound solitons, and tightly bound solitons. The beam profile of the output MM solitons in our experiment will not vary with the change of the pump power, PC orientation and the operating regime from CW to ML, whereas, the beam profiles are directly attributed to the MM segment state, rather than other factors (e. g., the operating state, PC state, pump power). Abstract: In this letter, we report the experimental realization of the spatiotemporal mode-locked (STML) operation in a hybrid all-fiber Er-doped laser cavity composing of both the single-mode (SM) and multimode (MM) fiber segments. In such a hybrid cavity, the locking of the longitudinal or transverse modes is realized by changing the state of polarization controller (PC) or the MMF segment. By adjusting the PC, three different kinds of multimode solitons at ∼ 1560 nm are generated, including the conventional solitons, loosely bound solitons, and tightly bound solitons. Moreover, the evolution of mode distribution for different soliton states are investigated and it is found that the beam profiles are exactly determined by the state of MMF segment, which are quite different from the previous researches in the full-MM fiber system where the beam profile can be affected by the operating states. The obtained results are beneficial for the further exploring the spatiotemporal nonlinear dynamics. And this all-fiber STML laser with flexible outputs have high potential for applications in telecommunications and fiber laser sources.